Reabilitação protética total utilizando o conceito de implantes em função imediata All-on-4 - Maló, Paulo (2009)
Introdution: Immediate function (insertion of implant, abutment and provisional crown on the same surgical step), is considered as the main revolution since the implementation of Implantology in the seventies.The rehabilitation of edentulous jaws remains today in many cases as a challenge. The loss of posterior teeth, generally in an early age, leads to alveolar bone loss and consequent pneumatisation of the maxillary sinus in the maxilla and superficialization of the mentonian nerve in the mandible, making it impossible to rehabilitate the posterior regions without bone reconstruction techniques. The All-on-4 concept was designed to overcome the patients anatomical limitations providing fixed prosthetic solutions supported by immediate function implants, avoiding complex techniques for increasing the bone volume. The focus of research, also centers on the development of new implant designs that allow increasing the treatment predictability, especially in clinical demanding situations, always with immediate function as background. In this case, the NobelspeedyTM implant constitutes an alternative. The aim of this work is to evaluate the All-on-4 concept for rehabilitation of edentulous jaws using implants in immediate function, and in the possible implementation of the NobelspeedyTM implant in immediate function protocols. Materials and Methods: With the objective of testing the support of the propositions that the prosthetic rehabilitation through the All-on-4 concept is possible and with a success and survival rates distribution similar to other rehabilitation protocols, three clinical studies were elaborated: All-on-4 Mandible (with 144 patients and 576 implants with 5 years of retrospective follow-up); All-on-4 Maxilla (with 157 patients with 628 implants and 3 years of retrospective follow-up); and All-on-4 Extra-maxilla (with 29 patients, 67 extra-long implants and 57 standard implants, with a prospective follow-up of up to 40 months). To test the support of the proposition that the development and implementation of the NobelspeedyTM implant in immediate function protocols on areas of bone less dense is possible, a patent for the development of a new implant (NobelspeedyTM) was created. Results: For the rehabilitation of the complete edentulous mandible through the All-on-4 Mandible concept, the implant and prosthesis success rates were 97% and 100% respectively, after 5 years of follow-up. For the rehabilitation of the complete edentulous maxilla through the All-on-4 Maxilla concept, the implant and prosthesis success rates were 97.5% and 100% respectively, after 3 years of follow-up. Regarding the rehabilitation of the complete edentulous atrophic maxilla through the All-on-4 Extra-maxilla concept, the implant and prosthesis success rates were 98.5% and 100% respectively, after a follow-up of up to 40 months. Regarding the NobelspeedyTM implant, it was possible to produce a patent for the development and implementation of the implant in immediate function protocols in areas of bone less dense. Discussion: The results achieved in the 3 clinical studies on the rehabilitation through the All-on-4 concept, allow us to support the propositions that the prosthetic rehabilitations through this concept is possible, with the distribution of the success and survival rates similar to other rehabilitation protocols, validating the All-on-4 mandible in the long-term follow-up, and the All-on-4 Maxilla and All-on-4 Extra-maxilla in the medium term-follow-up. The results from the patent analysis and specifically from the patent addendum, it was possible to verify that the NobelspeedyTM implant patent produced surplus values for the industry, the health professionals in the field of Implantology, and the patients, which allow us to support the proposition that the development and implementation of the NobelspeedyTM implant in immediate function protocols on areas of less dense bone is possible. Conclusion: The result of this work allow us to conclude that the All-on4 concept for the rehabilitation of the complete edentulous mandible, maxilla and atrophic maxilla is viable in the long term follow-up (mandible) and medium-term follow-up (maxilla and atrophic maxilla); thus the NobelspeedyTM implant constitutes a surplus value in Oral Implantology